A Multivariate Blind Ring Signature Scheme. (26th November 2019) - Hoang Duong, Dung; Susilo, Willy; Tran, Ha Thanh Nguyen
Abstract: Blind signatures are an important and useful tool in designing digital cash schemes and electronic voting protocols. Ring signatures on the other hand provide the anonymity of the signer within the ring of users. In order to fit to some real-life applications, it is useful to combine both protocols to create a blind ring signature scheme, which utilizes all of their features. In this paper, we propose, for the first time, a post-quantum blind ring signature scheme. Our scheme is constructed based on multivariate public key cryptography, which is one of the main candidates for post-quantum cryptography.